Business Ethics Challenges in Digital Disruption Era: A Case Study of Local Startups - Hariyadi Fajar Nugroho (Economics and Digital Business Review, 2026)
Empirical evidence on how early-stage startups in emerging markets operationalize business ethics amid rapid digital disruption remains limited. Addressing this gap, this study examines ethical challenges faced by Indonesian digital startups and how they manage them while pursuing growth. Using a qualitative multiple-case design, we studied five startups across fintech, edtech, healthtech, e-commerce, and digital marketing through in-depth interviews, document analysis, and non-participant observation. Within-case narratives and cross-case pattern matching reveal four recurrent issues: (1) managing data privacy and informed consent under evolving regulation, (2) ensuring transparency and accountability in AI-assisted decisions, (3) protecting intellectual property in fast-iterating partnerships, and (4) translating founders’ moral identity into day-to-day governance routines. Startups that embed simple but disciplined practices—data minimization, role-based access controls, audit logs, explainability measures, and clear retention policies—report stronger customer trust, fewer compliance frictions, and more resilient growth. The study contributes a context-specific framework of ethical leadership and governance for digital startups in emerging markets, clarifying practical checkpoints from inception to scaling and articulating trade-offs between speed and stewardship. These insights inform founders and policy makers seeking to sustain innovation without compromising ethical standards.